REVITALISASI ISTILAH TUMBUH-TUMBUHAN LANGKA DALAM PENGAJARAN BAHASA BALI, SEBAGAI UPAYA PELESTARIAN LINGKUNGAN HIDUP (KAJIAN EKOLINGUISTIK) - I Made Suweta (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractLanguage associated with the environment around us is highly correlated withecolinguistics study. Aspects of the direct contact with the rare plants are veryimportant from the point of view ecolinguistics study, therefore very importantthat the term of rare plants to be revitalized and can be incorporated in teaching,especially in terms of vocabulary learning. The formulation of the problem tobe studied are: (1) how the classification of rare plants term in vocabulary ofBalinese language? and (2) how to revitalize the term of rare plants in thelearning of Balinese language vocabulary ? The method used to discuss thispaper is listening vocabulary of rare plants as possible, either through speechcommunity understanding in Balinese language and literature over the scriptthrough the manuscrift of medicinal plants. The analysis was done by descriptivequalitative through integration between inductive and deductive method. Thispaper produces some results of the study as follows. Classification of rareplants, the term is described as follows: (1) related to Hindu religion, (2)residential building/sanctuary, (3) food/beverage, (4) agriculture/animalhusbandry, (5) sacred/magical, (6) drug-medicines. Descriptions in teachingBalinese terms are as follows: (1) the term two syllables, (2) three syllables, (3)four syllables, (4) five syllables, (5) The compound, and (6) repeatedword.